DESAFIOS E INQUIETAÇÕES DA DOCÊNCIA: A TRANSIÇÃO DE ALUNOS PÚBLICO-ALVO DA EDUCAÇÃO ESPECIAL DO 5º (QUINTO) PARA O 6º (SEXTO) ANO DO ENSINO FUNDAMENTAL - PRADO, LEIVA AYRES DO (2022)
This research aims at discussing the challenges and concerns that teachers experience in their pedagogical practices over the transition process of target-audience students of special education (TSSE), from the 5th (fifth) to the 6th (sixth) grade of elementary school. In order to achieve the goals proposed, qualitative research, of an interpretative character, was carried out in 2 (two) municipal schools and 1 (one) state school, all of them located in the urban area of the municipality of Prudentópolis, in the countryside of Paraná state. Questionnaires were applied and meetings were organized with a focus group as instruments for data collection, with the participation of 18 professionals, among them multifunctional resource room teachers (MRR), pedagogical coordinators and teachers of classes of the 5th (fifth) and 6th (sixth) grades of elementary school. A subsequent analysis was done from the theoretical-methodological approach of content analysis, proposed by Bardin (2016). As a theoretical basis for this research, a bibliographical revision and research of the state of knowledge on the object of study were carried out. Among the authors who served as theoretical support, the following stand out: Andrade (2011), Bardin (2016), Mantoan (2003), Bergamo (2012), Gatti (2005), Silva (2012), Glat (2011, 2018), Damas (2021), among others. The main results of the research indicated that the greatest challenges pointed out by the investigated teachers are lack of training, both initial and continued, in the area of special education, as well as lack of dialogue and articulation between the teachers of the 5th (fifth) and 6th (sixth) grades and the teachers in multifunctional resource rooms (MRR). These challenges pointed out by the teachers end up impacting the performance of teachers of regular classes with TSSE students, since they are not given enough tools and knowledge, by means of initial or continuing training, nor appropriate information about the needs, limitations and difficulties of TSSE students, which could arise from dialogue and articulation between the teachers that work with these students at schools. This lack of training, dialogue and articulated actions between these teachers end up preventing the transition process from the early years to the final years of elementary school from taking place more smoothly and generating less harm to the TSSE students. Another important result achieved was that, after applying the questionnaires with the teachers and carrying out meetings with the focus group, the Municipal Secretariat of Education of Prudentópolis/PR included, in its Political Pedagogical Project (PPP), the theme “Transition from preschool to elementary school - early years, and from elementary school - early years to final years”. In addition, teachers and pedagogical coordinators, research participants, reflected, debated and started several actions involving school, families and students, so that the transition process of TSSE students from the 5th (fifth) to the 6th (sixth) grade of elementary school becomes a moment of discoveries, welcoming and dialogue among all those involved.